Justification of the essence of professional self-improvement in the process of professional training of musical art teacher - Tusheva, Viktoriia (Professional Art Education, 2025)
The article examines the problem of professional self-improvement of a music teacher in new socio-cultural conditions, where culture and values take on priority importance. The essence of the concept of «professional self-improvement of a teacher of musical art» is revealed in philosophical, psychological and pedagogical aspects, the author’s interpretation of this personal phenomenon is given, and the relationship between professional self-improvement and the teacher’s professional culture is revealed. It is proven that the professional training of a future teacher of music, in which professional self-improvement occupies a dominant place as an integrating quality, acquires a new meaning, is characterized by cultural multi-vectority, trans-faithfulness, interdisciplinary nature, and integrity, and involves dialogical communication with various types, genres, styles, and directions of art, as well as musical works that have become history. It is shown that in this way the cognitive component and general intellectualization in the musical-performing process will be strengthened, reflective thinking will be formed and a “I-concept” of a musical work will be created in the performer’s mind, which in the complex will ensure professional self-improvement and self-development of the future teacher of musical art. Research methods. To achieve the goal, scientific methods were applied that create a kind of methodology of the selected research, namely: analytical in terms of studying the scientific fund; inductive-deductive and generalization in revealing the essential characteristics of the studied pedagogical phenomenon, its regularities of functioning and development; modeling method in creating a model of professional training for future teachers of music. The purpose and objectives of the article. The purpose of the article is to substantiate the essence and content of professional self-improvement of future teachers of musical art in the context of modern concepts; to define such key concepts of the study as «professional self-improvement», «self-education», «self-development», «professional self-realization», «professional culture»; identifying value priorities of professional training of music teachers as the main factor in their professional self-improvement. Results. The theory of professional self-improvement of future teachers of musical arts has been improved, thanks to the substantiation of theoretical provisions regarding the specified personal phenomenon; identifying the features of professional training, which is characterized by cultural multi-vector, trans-faith, interdisciplinary nature, in which attention is focused on musical performance and interpretation activities, which will influence the formation and development of professional self-improvement of a teacher-musician. The conclusions note that the concept of professional training becomes an effective means of forming professional self-improvement of a future teacher-musician, which requires re-thinking and updating in new socio-cultural conditions; the humanistic paradigm represents the theoretical and methodological basis for forming a strategy for professional training of a teacher, determining its content and technologies; the humanistic paradigm represents the theoretical and methodological basis for the formation of a strategy for professional teacher training, determining its content and technologies. Priority in professional training is given to musical performance activities, which involve the recognition and stabilization of the semantic structure of musical works, provided by phenomenological reflection, which is recognized as a prerequisite for the teacher's professional self-improvement. We consider the concept of «professional culture» as fundamental in revealing the essential characteristics of the professional self-improvement of a teacher-musician as a personal phenomenon that will influence the further professional self-development and self-realization of the artist. У статті досліджується проблема професійного самовдосконалення вчителя музичного мистецтва, яке у нових соціокультурних умовах, де культура і цінності набувають пріоритетного значення, виступає головним чинником у становленні професійної зрілості майбутнього фахівця. Розкрито сутність поняття «професійне самовдосконалення вчителя музичного мистецтва» у філософському, психологічному і педагогічному аспектах, дана авторська інтерпретація цього особистісного феномену, розкрито взаємозв’язок професійного самовдосконалення і професійної культури вчителя. Доведено, що фахова підготовка майбутнього вчителя музичного мистецтва, в якій професійне самовдосконалення займає домінантне місце як інтегруюча якість, набуває нового змісту, характеризується культурною багатовекторністю, трансфесійністю, міждисциплінарністю, цілісністю, передбачає діалогічне спілкування з різними видами, жанрами, стилями і напрямами мистецтва, музичними творами, які стали історією. Показано, що у такий спосіб буде посилюватися когнітивна складова і загальна інтелектуалізація у музично-виконавському процесі, формуватися рефлексивне мислення і створюватися у свідомості виконавця «Я-концепція» музичного твору, що в комплексі забезпечить професійне самовдосконалення і саморозвиток майбутнього вчителя музичного мистецтва. Методи дослідження. Для досягнення мети були застосовані наукові методи, які створюють своєрідну методику обраного дослідження, а саме: аналітичні щодо вивчення наукового фонду; індуктивно-дедуктивний і узагальнення у розкритті сутнісних характеристик досліджуваного педагогічного явища, його закономірностей функціонування та розвитку; метод моделювання у створенні моделі фахової підготовки майбутніх учителів музичного мистецтва. Мета і завдання статті. Метою статті є обґрунтування сутності і змісту професійного самовдосконалення майбутніх учителів музичного мистецтва в контексті сучасних концепцій; визначення таких ключових понять дослідження як «професійне самовдосконалення», «самовиховання», «саморозвиток», «професійна самореалізація», «професійна культура»; виявлення ціннісних пріоритетів фахової підготовки вчителів-музикантів як головного чинника їх професійного самовдосконалення. Результати. Удосконалено теорію професійного самовдосконалення майбутніх учителів музичного мистецтв, завдяки обґрунтуванню теоретичних положень щодо зазначеного особистісного феномену; виявленні особливості фахової підготовки, яка характеризується культурною багатовекторністю, трансфесійністю, міждисциплінарністю, в якій акцентується увага на музично-виконавській та інтерпретаційній діяльності, що вплине на формування і розвиток професійного самовдосконалення вчителя-музиканта. У висновках зазначається, що поняття фахова підготовка стає дієвим засобом формування професійного самовдосконалення майбутнього вчителя-музиканта, яка потребує переосмилення і оновлення в нових соціокультурних умовах; гуманістична парадигма представляє теоретико-методологічне підґрунтя формування стратегії фахової підготовки учителя, визначаючи її зміст і технології. Пріоритетне значення у фаховій підготовці займає музично-виконавська діяльність, яка передбачає визнання й устабільнення смислової структури музичних творів, забезпечується феноменологічною рефлексією, яка визнається передумовою професійного самовдосконалення вчителя. Розглядаємо поняття «професійна культура» як засадниче у розкритті сутнісних характеристик професійного самовдосконалення вчителя-музиканта як особистісного феномену, що вплине на подальший професійний саморозвиток і самореалізацію митця.